Retinal nerve fiber layer thickness and visual hallucinations in Parkinson's Disease. Issue 1 (17th June 2013) - Lee, Jee‐Young; Kim, Jae Min; Ahn, Jeeyun; Kim, Han‐Joon; Jeon, Beom S.; Kim, Tae Wan
ABSTRACT Defective visual information processing from both central and peripheral pathways is one of the suggested mechanisms of visual hallucination in Parkinson's disease (PD). To investigate the role of retinal thinning for visual hallucination in PD, we conducted a case‐control study using spectral domain optical coherence tomography. We examined a representative sample of 61 patients with PD and 30 healthy controls who had no history of ophthalmic diseases. General ophthalmologic examinations and optical coherence tomography scans were performed in each participant. Total macular thickness and the thickness of each retinal layer on horizontal scans through the fovea were compared between the groups. In a comparison between patients with PD and healthy controls, there was significant parafoveal inner nuclear layer thinning, whereas other retinal layers, including the retinal nerve fiber layer, as well as total macular thicknesses were not different. In terms of visual hallucinations among the PD subgroups, only retinal nerve fiber layer thickness differed significantly, whereas total macular thickness and the thickness of other retinal layers did not differ. The retinal nerve fiber layer was thinnest in the group that had hallucinations without dementia, followed by the group that had hallucinations with dementia, and the group that had no hallucinations and no dementia. General ophthalmologic examinations did not reveal any significant correlation with hallucinations. There were no significant correlations between retinal thicknesses and duration or severity of PD and medication dosages. The results indicate that retinal nerve fiber layer thinning may be related to visual hallucination in nondemented patients with PD. Replication studies as well as further studies to elucidate the mechanism of thinning are warranted. © 2013 International Parkinson and Movement Disorder Society